Catalytic SNAr Hydroxylation and Alkoxylation of Aryl Fluorides. Issue 37 (11th August 2021) - Kang, Qi‐Kai; Lin, Yunzhi; Li, Yuntong; Xu, Lun; Li, Ke; Shi, Hang
Abstract: Nucleophilic aromatic substitution (SN Ar) is a powerful strategy for incorporating a heteroatom into an aromatic ring by displacement of a leaving group with a nucleophile, but this method is limited to electron‐deficient arenes. We have now established a reliable method for accessing phenols and phenyl alkyl ethers via catalytic SN Ar reactions. The method is applicable to a broad array of electron‐rich and neutral aryl fluorides, which are inert under classical SN Ar conditions. Although the mechanism of SN Ar reactions involving metal arene complexes is hypothesized to involve a stepwise pathway (addition followed by elimination), experimental data that support this hypothesis is still under exploration. Mechanistic studies and DFT calculations suggest either a stepwise or stepwise‐like energy profile. Notably, we isolated a rhodium η 5 ‐cyclohexadienyl complex intermediate with an sp 3 ‐hybridized carbon bearing both a nucleophile and a leaving group. Abstract : A rhodium‐catalyzed hydroxylation of aryl fluorides via η 6 ‐coordination was achieved. This method was also applicable in the alkoxylation. A Meisenheimer‐type intermediate was successfully isolated and well characterized. Density functional theory calculations and mechanistic studies suggested a stepwise or stepwise‐like energy profile for the SN Ar reaction.